2013
DOI: 10.1094/pdis-09-12-0823-re
|View full text |Cite
|
Sign up to set email alerts
|

Root Rot of Pea and Faba Bean in Southern Sweden Caused by Phytophthora pisi sp. nov.

Abstract: Heyman, F., Blair, J. E., Persson, L., and Wikström, M. 2013. Root rot of pea and faba bean in southern Sweden caused by Phytophthora pisi sp nov. Plant Dis. 97:461-471..'.>/' F i>-A root rot disease of pea and faba bean caused by a Phytophthora sp. was observed in fields and field soil samples in southern Sweden.Observations of the disease in pea root rot greenhouse assays were systematically recorded, and incidence and geographic distribution data were compared with the pea root rot caused by Aphanomyces eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
18
0
3
Order By: Relevance
“…The use of coalescent-based approaches to estimate species trees from a collection of gene trees has been gaining popularity among many other taxonomic groups, but has seen little attention in Phytophthora or oomycete research in general. The recent description of P. pisi (Heyman et al 2013) employed a multispecies coalescent approach, which confirmed the individual analyses of ITS and cox2 data. In addition, a recent study of the hybrid species P. andina (Blair et al 2012) used several coalescent methods to determine the likely parental lineages of this species, one of which was clearly P. infestans.…”
Section: Molecular Phylogenysupporting
confidence: 56%
See 1 more Smart Citation
“…The use of coalescent-based approaches to estimate species trees from a collection of gene trees has been gaining popularity among many other taxonomic groups, but has seen little attention in Phytophthora or oomycete research in general. The recent description of P. pisi (Heyman et al 2013) employed a multispecies coalescent approach, which confirmed the individual analyses of ITS and cox2 data. In addition, a recent study of the hybrid species P. andina (Blair et al 2012) used several coalescent methods to determine the likely parental lineages of this species, one of which was clearly P. infestans.…”
Section: Molecular Phylogenysupporting
confidence: 56%
“…Additional species have recently been described; P. lacustris (Nechwatal et al 2012) P. pluvialis (Reeser et al 2013), P. mississippiae , P. cichorii, P. dauci and P. lactucae (Bertier et al 2013), P. pisi (Heyman et al 2013), P. stricta and P. macilentosa ) and the hybrid species P. x serendipita and P. x pelgrandis (Man in 't Veld et al 2012), bringing the total to at least 128 described species. With the number of provisional species names used in the literature, and research efforts to evaluate the distribution of this genus in natural ecosystem, this number is likely to continue to increase in the future.…”
Section: Recommendationsmentioning
confidence: 99%
“…27) A new Phytophthora species isolated from 33 host species in 25 families from Australia, Hungary, Israel, Italy, Japan, the Netherlands, Norway, South Africa, Spain, Taiwan, Turkey, the United Kingdom and United States is newly described as Phytophthora niederhauserii. P. niederhauserii is a distinct species based on morphological comparisons of isolates of this species with descriptions published for 134 Phytophthora taxa, including recently described species such as P. (Nechwatal et al 2013), P. mississippiae X. Yang, W. E. Copes, and C. X. Hong (Yang et al 2013), P. parvispora Scanu and Denman (Scanu et al 2014), P. pisi F. Heyman (Heyman et al 2013) and P. pluvialis Reeser, Sutton and E Hansen (2013), as well as other putative novel species. Phytophthora niederhauserii is self-sterile (heterothallic), fast growing and a high temperature-adapted species that produces non-papillate, mostly ellipsoid, persistent, proliferating sporangia, and has unique toruloid lobate irregular branched hyphal swellings.…”
Section: Resultsmentioning
confidence: 94%
“…Lack of affinity for genistein and daidzein in P. pisi is consistent with its lack of pathogenicity on soybean and cowpea. The pathogenicity of P. pisi towards pea, faba bean and lentil seen in this study is consistent with results reported earlier (Heyman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, when it comes to interactions between legumes and nodule‐forming bacteria, different isoflavones in root exudates can act synergistically as nodulation gene inducers but also in an antagonistic manner as anti‐inducers (Cooper, ), and similar interaction effects between isoflavones may be expected for Phytophthora species. The difference in response to genistein and daidzein between P. pisi and P. sojae may be a recent adaptation, as these species are reported to be closely related sister taxa (Heyman et al ., ).…”
Section: Discussionmentioning
confidence: 97%